THE INFLUENCE OF RELIGION AND COMMUNITY BEHAVIOR ON ELECTION SUCCESS IN WEST JAVA IN 2019 - Nassarudin, E Hasbi; Anggraeni, Leni; Mayaningsih, Dewi (VARIA HUKUM, 2024)
The history of the development of elections from the point of view of voters based on 5 elections, that there is polarization and changes in behavior. Judging from the elections that were carried out at first those who were Muslims supported parties labeled Islam, but gradually the selection of parties began to move to parties that were not labeled Islam. It can be seen by the number of parties that have emerged in several elections that have been held, most of the parties that have emerged are not directly based on Islamic principles, but rather choose a party style that is nationalistic. It is not impossible that the shift is caused by various factors, both external and internal factors. According to Sutidi Ridha in his research results concluded that behavior. This research tries to guess and analyze religious factors and community behavior towards the success of elections in 2019.Sejarah perkembangan pemilu dari sudut pandangan pemilih berdasarkan 5 kali pemilu, bahwa terjadi polarisasi dan perubahan perilaku. Dilihat dari pemilihan yang dilakukan padamulanya mereka yang bergama Islam mendukung partai yang berlabel Islam, namun secara bertahap pemilihan partai mulai berpindah kepada partai yang bukan berlabel Islam. Dapat dilihat dengan banyaknya partai yang muncul pada beberapa kali pemilu yang telah dilaksanakan, kebanyakan dari partai yang muncul tidak langsung berlandaskan kepada asas-asas Islam, namun lebih banyak memilih corak partai yang bersifat nasionalisme. Bukan tidak mungkin adanya pergeseran tersebut disebabkan karena berbagai macam faktor, baik faktor eksternal ataupun faktor internal. Menurut Sutidi Ridha dalam hasil penelitiannya menyimpulkan bahwa perilaku. Penelitian ini mencoba untuk mengungkap dan menganalisis faktor agama dan perilaku masyarakat terhadap keberhasilan pemilu pada tahun 2019.